Celebrating Adam Watkins First Birthday in Watkins' Backyard - Watkins, Howard::::::::: (1979)
Christine Watkins, Howard Watkins viewing television showing video of Adam Watkins' birth Christine with long hair; Howard with Afro hairstyle